2015
DOI: 10.1007/s10854-015-3583-1
|View full text |Cite
|
Sign up to set email alerts
|

High performance resistive switching memory organic films prepared through PPy growing on graphene oxide substrate

Abstract: In this study, the photochemical polymerization using graphene oxide (GO) as initiator generates a new composite film with polypyrrole (PPy) covering the GO nanosheets. The specular reflection infrared spectroscopy reveals the continuous upload of the conjugated polymers. Structures of the as-synthesized films are studied by using Raman and X-ray photoelectron spectroscopy with the aim of gaining an insight into the interface. The electronic properties of the composite films are investigated using solid-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The other is G‐band at 1590 cm −1 attributed to the sp 2 hybrid carbon . The change of intensity ratio of the two peaks (I D /I G ) is commonly used to observe changes in the conjugated structure of carbon nanoparticles . It is noticeable that the I D /I G of CNTs‐2 is higher than that of CNTs‐1, which assures that the conjugated structure of CNTs is disrupted by adsorption of ACMs through electrostatic and π–π interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The other is G‐band at 1590 cm −1 attributed to the sp 2 hybrid carbon . The change of intensity ratio of the two peaks (I D /I G ) is commonly used to observe changes in the conjugated structure of carbon nanoparticles . It is noticeable that the I D /I G of CNTs‐2 is higher than that of CNTs‐1, which assures that the conjugated structure of CNTs is disrupted by adsorption of ACMs through electrostatic and π–π interactions.…”
Section: Resultsmentioning
confidence: 99%
“…46 This behavior can be associated with a number of defects/traps in the material previously reported for rGO materials, such as the Poole−Frenkel effect, 47 Fowler− Nordheim tunneling, 48 and a space-charge-limited emission. 49,50 We also note that the samples prepared from pristine GO (no prior POEGMA modification, Figure 1F) and having higher C/O ratio demonstrate much lower value of conductivity (Figure 3D). From the linear portion of the I−V curve (between −0.5 and +0.5 V) we estimated the sheet resistance values for rGO-P monolayers to be 23.8 kΩ/sq, and then, taking into account the thickness of individual rGO-P sheets, we found the average conductivity to be only 580 S/cm (Table S1).…”
Section: ■ Results and Discussionmentioning
confidence: 87%
“…An intimate interface has been regarded to promote both electron transfer and the stability of the devices. 16 Several methods have been developed for preparing the GOconductive polymer composites for RRAM devices. The carboxylic acid groups at the surface of GO have been usually chosen as the reaction sites.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we have reported a straightforward, one-step method to prepare the composite lms of polypyrrole (PPy) and GO by using in suit photopolymerization. 16 Having realized the fact that GO is in nature of semiconductor and shows the photocatalytic ability, we used the photoexcitated GO to successfully initiate the polymerization of pyrrole. The results showed that the as-synthesized PPy strongly interacted with the GO substrate serving as the initiator, and the composite lms devices exhibited the RRAM properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation